Egyptian name scarabs from the 12th to the 15th Dynasty: geography and chronology of production - Il'in-Tomič, Aleksandr A. (Contributions to the archaeology of Egypt, Nubia and the Levant, 2023)
Cover -- Title page -- Table of Contents -- Preface and acknowledgements -- Introduction -- Re-examination of scarabs in museums -- Scarab classifications -- Scarab collections and collectors -- 1. Name scarabs of the 12th-13th Dynasty: the chronology of production -- Development from Sobekhotep III to Ay -- Pre-Sobekhotep III name scarabs -- Scarabs of the king Sehetepibre -- Spellings of the word bjtj with the sign "red crown" (S3) -- Comparison of 12th and 13th Dynasty scarabs -- Results: how precisely can one date scarabs? -- Dating criteria for private-name scarabsbased on available evidence -- 2. Late Middle Kingdom private-name scarabs: the geography of production -- Traits better attested on scarabs ofnorthernersContinuous scroll borders (1a-1j, 4c bases) andthe start of private-name scarab use in southernUpper Egypt -- Memphis-Faiyum groups of scarabs -- Traits better attested on scarabs of southernUpper Egyptians -- Southern Upper Egyptian groups of scarabs -- Results: centralised and local production ofscarabs in the Middle Kingdom -- 3. Name scarabs of the 14th-15th Dynasty: the chronology of production -- Scarabs of a '3-wsr- r' Apep -- Scarabs of the king Hotepibre -- Features of 14th-15th Dynasty scarabs -- Private-name scarab series -- Can a seriation of royal-name scarabs solvethe chronological conundrum? -- Excavated scarabs from Tell el-Dabʿa androyal-name scarabs -- 4. Name scarabs of the Second Intermediate Period: the geography of production -- Scarabs from Tell el-Dabʿa -- Scarabs from Tell el-Yahudiya -- Results: regional diversity in the SecondIntermediate Period -- 5. Scarabs as seen by their producers -- Perceived and unperceived scarab traitsand the standardisation of scarabs under the13th Dynasty -- Dwelling on the past: 12th Dynasty royalnamescarabs in the Second IntermediatePeriod.